KALIMAT TANYA INFORMATIF BAHASA INGGRIS DAN BAHASA INDONESIA: SUATU KAJIAN KONTRASTIF - , Hajjah Zulianti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is intended to describe the formation of English and Indonesian Informative interrogative sentences, to describe the similarities and differences of English and Indonesian Informative interrogative sentences, and to describe the consequence of the differences between English and Indonesian informative interrogative sentences. In collecting the data, the researcher uses observation method and recording technique. The English informative interrogative sentences are collected from the English grammar books